Pathogenesis of Streptococcus urinary tract infection depends on bacterial strain and β-hemolysin/cytolysin that mediates cytotoxicity, cytokine synthesis, inflammation and virulence - Leclercq, Sophie Y. (Sci Rep, 2016)
Streptococcus agalactiae can cause urinary tract infection (UTI) including cystitis and asymptomatic bacteriuria (ABU). The early host-pathogen interactions that occur during S. agalactiae UTI and subsequent mechanisms of disease pathogenesis are poorly defined. Here, we define the early interactions between human bladder urothelial cells, monocyte-derived macrophages, and mouse bladder using uropathogenic S. agalactiae (UPSA) 807 and ABU-causing S. agalactiae (ABSA) 834 strains. UPSA 807 adhered, invaded and killed bladder urothelial cells more efficiently compared to ABSA 834 via mechanisms including low-level caspase-3 activation, and cytolysis, according to lactate dehydrogenase release measures and cell viability. Severe UPSA 807-induced cytotoxicity was mediated entirely by the bacterial β-hemolysin/cytolysin (β-H/C) because an β-H/C-deficient UPSA 807 isogenic mutant, UPSA 807ΔcylE, was not cytotoxic in vitro; the mutant was also significantly attenuated for colonization in the bladder in vivo. Analysis of infection-induced cytokines, including IL-8, IL-1β, IL-6 and TNF-α in vitro and in vivo revealed that cytokine and chemokine responses were dependent on expression of β-H/C that also elicited severe bladder neutrophilia. Thus, virulence of UPSA 807 encompasses adhesion to, invasion of and killing of bladder cells, pro-inflammatory cytokine/chemokine responses that elicit neutrophil infiltration, and β-H/C-mediated subversion of innate immune-mediated bacterial clearance from the bladder.